RHETORICAL MOVES AND LINGUISTIC FEATURES OF JOURNAL ARTICLE ABSTRACTS BY POSTGRADUATE STUDENTS, NATIONAL AND INTERNATIONAL AUTHORS IN APPLIED LINGUISTICS - Rosyi Putri Andika; Safnil Arsyad; Alamsyah Harahap (Universitas Bengkulu, 2018)
The abstract has become the first part that will be read by readers in a research article. Some important aspects in the abstract are move structure and linguistic features. This study examines the rhetorical moves and linguistic features of English research article abstract written by three groups of authors in Applied Linguistics. The research design was mixed method design combining quantitative and qualitative method with the corpus of this study consisted of 60 abstracts by postgraduate students, national and international authors found in RA abstracts. The results show that the common moves by three groups of authors have only three moves (i.e purpose, method, and results). The common linguistic features used by three groups of authors are active voice, present tense, and simple sentence. By comparing the three groups of abstracts the differences are found in the postgraduate students authors. They were used move 1 (Background/ introduction/ situation) fewer than national and international authors. Furthur the postgraduate students used past tense more dominant than present tense and using hedges is more frequently than national and international authors. This study concludes that in writing RA abstracts a writer should adjust the commonly used rules the abstract especially in using 5 moves in the abstracts.